A mathematical model for evaluation of intelligence products value. Issue 4 (19th May 2018) - Korać, Dragan; Cica, Djordje
Abstract: In this paper is given a comprehensive approach devoted to mathematical application in intelligence science. One of the toughest challenges faced by intelligence analysis is the evaluation of the intelligence products value. This paper has given a novel mathematical model with which is possible to mitigate problems of uncertainty management in intelligence analysis. This model encompasses two key factors: accuracy and confidence that are particularly considered dependent on time. For computing crisp value of confidence factor, innovative fuzzy methodology is used in form of fuzzy expert system (FES). In addition, for the examined four extreme cases, the results show usefulness of this study. Finally, the given mathematical model significantly contributes deeper understanding of intelligence products terms and their mutual relations as well.